The utilization of provider-initiated testing counselling services for citizens at risk of HIV/aids at the polyclinic of class IIA Abepura penitentiary in Papua province - John Toding Padang; Agung Waluyo; Sri Yona; Aria Kekalih; Nurul Huda (Journal of the Pakistan Medical Association, 2024)
Objective: To analyse the factors related to the use of provider-initiated test and counselling services for inmates at high risk of HIV /AIDS. Method: This descriptive cross-sectional study was conducted at the Polyclinic of Class IIA Abepura Correctional Institution, Papua Province, Indonesia, from November to December 2020, and involved 140 inmates, of age 18 years or older selected by simple random sampling technique, at high risk of HIV after obtaining informed consent. All had been tested for HIV status were fluent in Indonesian and willing to participate in the study. The use of provider-initiated testing and counselling services was recorded in 112 (80%) cases. Data were collected using a structured questionnaire exploring aspects related to testing and counselling. Data were analysed using SPSS v.21. Results: The association between use of provider-initiated testing and counselling services and acceptance of HIV/AIDS related stigma and discrimination was significant (odds ratio=20.781; p<0.001). The association between use of provider-initiated testing and counselling services was also significant with belief in its usefulness (odds ratio=12.372; p<0.001), family and institutional support (odds ratio = 9.993; p<0.001), need for services (odds ratio = 6.587; p<0.001), and knowledge of services (odds ratio = 6.130; p<0.001). Conclusion: It is essential to build a cross-programme collaboration between health workers and security officers in the form of regular counselling to reduce the stigma and discrimination among inmates. Keywords: Immunodeficiency, Odds Ratio, Counselling, HIV, Prisoners.